2016
DOI: 10.1039/c5ay03380b
|View full text |Cite
|
Sign up to set email alerts
|

In-syringe reversed dispersive liquid–liquid microextraction coupled to high performance liquid chromatography for the determination of sulfonylurea herbicide residues in cereal samples

Abstract: A rapid and sensitive method, IS-R-DLLME coupled to HPLC, has been developed for the determination of sulfonylurea herbicides in cereal samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Dispersive liquid-liquid microextraction (DLLME) is an e cient and fast liquid-phase microextraction method proposed by Rezaee (Rezaee, et al, 2006) in 2006. The main improvement work is concentrated on innovating the dispersion method (Psillakis, 2019;Saleh, et al, 2009;Zhong, et al, 2019), updating the phase separation method (Guo, et al, 2016;Ngaosi, et al, 2016;Rezaee, et al, 2012;Ye, et al, 2016;Zhong, et al, 2019), and the usage of low-toxic extractants as much as possible. The ionic liquid (Marcinkowska, et al, 2019) which was used to replace the toxic extractant in DLLME (Montalbán, et al, 2018;Wu, et al, 2013) was found to be harmful to environment recently (Montalbán, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dispersive liquid-liquid microextraction (DLLME) is an e cient and fast liquid-phase microextraction method proposed by Rezaee (Rezaee, et al, 2006) in 2006. The main improvement work is concentrated on innovating the dispersion method (Psillakis, 2019;Saleh, et al, 2009;Zhong, et al, 2019), updating the phase separation method (Guo, et al, 2016;Ngaosi, et al, 2016;Rezaee, et al, 2012;Ye, et al, 2016;Zhong, et al, 2019), and the usage of low-toxic extractants as much as possible. The ionic liquid (Marcinkowska, et al, 2019) which was used to replace the toxic extractant in DLLME (Montalbán, et al, 2018;Wu, et al, 2013) was found to be harmful to environment recently (Montalbán, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various modes of HPLC have been successfully employed for vessels [20,29,30]. Thus far, the simplest reported extraction devices are syringes and syringes with pipet tip on top [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our lab has reported a fully automated method for the identification of phosphopeptides from cell lysate using INtip technology [14]. Much of the previous work with dSPE tips employed organic solvents to aid subsequent separations [15,16]. None of these studies, however, has demonstrated the use of dSPE for biomacromolecule purification from cell lysates.…”
mentioning
confidence: 99%